The effect of pre-operative physiotherapy on the early functional outcome of primary total knee arthroplasty - Ismail, Mohd Shukry; Sharifudin, Mohd Ariff; Ahmad Shokri, Amran (2013)
Introduction: Physiotherapy is an important part of rehabilitation following total knee arthroplasty (TKA). However, the significant impact of pre-operative physiotherapy on the functional outcomes of arthroplasty surgery is still debatable. This study evaluated the effect of pre-operative physiotherapy on the early functional outcome of primary TKA.